Globalization and sustainability : the collapse of the myth of compatibility. (1999)
The process of economíc globalization and the theme of sustainable development are the products of economic and environmenta/ transformatíons over long periods. We present and critically discuss the idea of promoting sustainable development through free trade (the agenda of GATT, the Rio Conference and the WTO). We pUl forward the proposition that the globalization that has taken place over the last decade is not sustalnable either for the South, or for future generations, and not even for the North. Sustainable development ís defined as necessarily Ine/uding two dímensions: social sustalnability and environmental sustainabilíty. The conflictual network of non-state and state actors can enable a movement towards environmental sustainability. The attainment of social sustainability is much more problema tic, beca use capitalism does not have, and has never had, the self regulatory mechanisms that allows capital accumulation to be oriented towards social progress. We put forward the idea that sustainable development cannot be a realistic objective unless it is promoted as an "international public good". But in the absence of either a hegemon (in the sense of Kindleberger), or of really strong international institutions or regimes, it is difficult to envisage a clear evolution for the future.